1994
DOI: 10.1073/pnas.91.9.3799
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive CpG suppression in animal mitochondrial genomes.

Abstract: AU available complete mitochondrial genomes (21 species) are evaluated for dinucleotide over-and under-representation. The CpG dinucleotide is pervasively under-represented in all animal mitochondria, but it is of variable relative abundance in fungal, protist, and plant mitochondrial genomes. Interpretations and hypotheses are considered relative to mitochondrial genome organization, methylation, structural specificities, directed mutation, and evolutionary events. In particular, our results support Mycoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
130
1
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(137 citation statements)
references
References 20 publications
1
130
1
5
Order By: Relevance
“…Animal (vertebrate and invertebrate) mt sequences show significant underrepresentations of CG dinucleotides, * CG Ϸ 0.40 to 0.60 (13), almost to the same extent as occurs in vertebrate genomic sequences. The adjusted D. melanogaster and (unadjusted) D. yakuba mt genomes entail * CG ϭ 0.73 and 0.68, respectively (13).…”
Section: Comparisons Of Mt Genomes Between Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal (vertebrate and invertebrate) mt sequences show significant underrepresentations of CG dinucleotides, * CG Ϸ 0.40 to 0.60 (13), almost to the same extent as occurs in vertebrate genomic sequences. The adjusted D. melanogaster and (unadjusted) D. yakuba mt genomes entail * CG ϭ 0.73 and 0.68, respectively (13).…”
Section: Comparisons Of Mt Genomes Between Speciesmentioning
confidence: 99%
“…The adjusted D. melanogaster and (unadjusted) D. yakuba mt genomes entail * CG ϭ 0.73 and 0.68, respectively (13). The fungal S. pombe has * CG ϭ 0.54 typical of animal mitochondria.…”
Section: Comparisons Of Mt Genomes Between Speciesmentioning
confidence: 99%
“…Recent work from our laboratory suggested that this B-cell stimulation was mediated by a 6-base nt motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines (12). This motif is expressed nearly 20 times more frequently in bacterial than vertebrate DNA (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from our laboratory suggested that this B-cell stimulation was mediated by a 6-base nt motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines (12). This motif is expressed nearly 20 times more frequently in bacterial than vertebrate DNA (12)(13)(14).In addition to B-cell activation, the innate immune response to bacterial infection is characterized by the production of immunomodulatory cytokines (15,16). These include interleukin (IL) 6, which contributes to T-and B-cell activation (17-20), IFN-y, which (25)(26)(27).…”
mentioning
confidence: 99%
“…The bioactive molecular entities were identified as being palindromic nucleotide sequences containing a cytosine-phosphate-guanosine (CpG) core [3]. These sequences are highly frequent in non-vertebrate DNA but are rare in vertebrate DNA [4,5]. Synthetic oligodeoxynucleotides (ODNs) that contain such CpG motifs (CpG ODNs) induce B-cell proliferation, interleukin-6 (IL-6) production and antibody [immunoglobulin (Ig)] secretion in vitro [4,6].…”
Section: Introductionmentioning
confidence: 99%